1987
DOI: 10.1164/ajrccm/136.6.1486
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects and Sources of Indoor Air Pollution. Part I

Abstract: Since the early 1970s, the health effects of indoor air pollution have been investigated with increasing intensity. Consequently, a large body of literature is now available on diverse aspects of indoor air pollution: sources, concentrations, health effects, engineering, and policy. This review begins with a review of the principal pollutants found in indoor environments and their sources. Subsequently, exposure to indoor air pollutants and health effects are considered, with an emphasis on those indoor air qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
1
7

Year Published

1994
1994
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(175 citation statements)
references
References 52 publications
2
165
1
7
Order By: Relevance
“…Ninety-three percent of the valley homes had an air conditioner in contrast to only one mountain home. Associations between house characteristics and indoor/outdoor ratios for NO 2 and O 3 are shown in Table 4. The indoor/outdoor ratios for HONO were not evaluated because only 14 houses had both indoor and outdoor HONO levels above the detection limit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ninety-three percent of the valley homes had an air conditioner in contrast to only one mountain home. Associations between house characteristics and indoor/outdoor ratios for NO 2 and O 3 are shown in Table 4. The indoor/outdoor ratios for HONO were not evaluated because only 14 houses had both indoor and outdoor HONO levels above the detection limit.…”
Section: Resultsmentioning
confidence: 99%
“…In April and May 1996, HONO, NO 2 and O 3 concentrations were measured in 119 homes. The homes were recruited from an ongoing 12-month study measuring indoor and outdoor concentrations and personal exposure to ozone of elementary school-age children in two communities in Southern California.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…jii Another source of NO 2 pollution that has gained recognition is the use of gas-fired appliances in the home which may produce NO 2 levels greater than 4 ppm (Samet et al, 1987;Leaderer et al, 1984). Studies which exposed humans to ambient levels of 0.5-7.5 ppm for 10 min to 2 h have demonstrated increases in airway resistance, decreases in lung compliance and diffusing capacity, but only at the higher concentrations (>2.5 ppm) (Von Neiding et al, 1970;Beil and Ulmer, 1976;Abe, 1976).…”
Section: Epidemiologymentioning
confidence: 99%
“…In the mid-twentieth century, striking increases in mortality followed a series of severe air pollution incidents in the US and Europe [2,3]. By the early 1990s, time series studies [4][5][6][7] of single locations have demonstrated that even lower air pollution levels increase the rates of mortality and morbidity throughout the developed countries. Air pollution is due to a heterogeneous mixture of gaseous and particulate components.…”
Section: Introductionmentioning
confidence: 99%